Studies of the Electrochemical Degradation of Acetaminophen Using a Real-Time Biomimetic Sensor - Quintino de Oliveira, Mariana Calora [UNESP]; Tanaka, Auro Atsushi; Roberto de Vasconce los Lanza, Marcos; Taboada Sotomayor, Maria Del Pilar [UNESP] (Wiley-Blackwell, 2011)
Real-time monitoring of the electrochemical degradation of acetaminophen was performed using a biomimetic sensor coupled to a flow injection analysis (FIA) system. Degradation of the drug was carried out at constant current density (24 to 180 mAcm(-2)) in an electrolyte consisting of 0.1 molL(-1) K(2)SO(4)/5.0 x 10(-4) molL(-1) FeSO(4)center dot 7H(2)O. Two commercial DSA anodes (DSA-Cl(2) and DSA-O(2)) were compared. The degradation process was monitored online using an amperometric sensor based on the biomimetic catalyst iron(III) tetrapyridinoporphyrazine (FeTPyPz), coupled to the degradation cell. The optimized FIA detection system employed the electrolyte solution as carrier, a flow rate of 1.25 mLmin(-1) and an injected sample volume of 75 mu L. The real-time data obtained showed, as expected, that acetaminophen degradation followed pseudo-first order kinetics, with the DSA-Cl(2) anode showing a higher efficiency according to the calculated apparent rate constant values. The advantage of the proposed on-line system is that a larger number of points can be monitored in a shorter time compared to other off-line methods, which improves the accuracy of estimates of electrochemical degradation constants.
Keywords: Acetaminophen; Electrochemical degradation; DSA anodes; Biomimetic sensors; On-line monitoring